De Troia a Constantinoble: Aquil.les i Tirant en l'amor i en la guerra - Perujo Melgar, Joan M. (Caplletra: revista internacional de filología, 1997)
The importanee of Guido delle Colonne's HistòriesTroianes in the creation of the medieval mythical chivalresque universe can be studied in differernt literary works as in Tirant lo Blanch. By means of the semiotic method used in other works, the author establishes a particular parallelism between Tirant and Achilles in respect to their military and affectionate behaviour. Both heroes share similar literary stages: a process of falling in love which culminates in the traditional 'love sickness' and, therefore, in the abandonment of military duties. This behaviour warrants punishment: to be killed after walking into an ambush (Achilles's case) and a journey of atonement to Northern Africa (in Tirant lo Blanch).